PERLINDUNGAN HUKUM TERHADAP MEREK TERKENAL ASING DI INDONESIA (STUDI KASUS PUTUSAN MAHKAMA AGUNG NOMOR: 165/Pdt.Sus-Hki/2016 DAN PUTUSAN MAHKAMA AGUNG NOMOR: 557K/Pdt.sus-HKI/2015) - Ronald Kurniawan; Simona Bustani (Jurnal Hukum Adigama, 2019)
The first dispute with Case Number MA Decree 557 K / Pdt.Sus-HKI / 2015 that occurred between the designer clothing (designer) from France, Pierre Cardin owner of the Brand Business Pierre Cardin as the claimant, whose brand is a popular brand and has been used since the beginning In March 1974, in this matter the prosecutor against the defendant Alexander Satryo Wibowo, was a local businessman who owned the Trademark Pierre Cardin, who had registered his trademark since July 29, 1977 in Indonesia, where there were similarities in essence or overall in the use of the trademark between the claimant and defendant. Therefore Pierre Cardin, hereby as the prosecutor, demanded the cancellation of the registered mark Card Pierre Cardin used by the defendant, against this demand the Commercial Court at the Central Jakarta District Court has determined the determination of Ms. 15 / Pdt.Sus-Trademark / 2015 / PN.Niaga.Jkt .Pst., Dated June 9, 2015 which in the main issue rejected the claim of the prosecutor for the whole. Furthermore, the Plaintiff requested the appeal of the appeal to the Supreme Court. Legal remedies requested by the claimant in accordance with the provisions of Chapter 6 point (3) letter b of Law Number 15 of 2001 concerning Trademarks. In carrying out the appeal appeal law, the Supreme Court has decided on decision number 557 K / Pdt.Sus-HKI / 2015 which in its stipulation stipulates rejecting an appeal request from the appealer Pierre Cardin.